A Methods engineering study on Imperial Plastic Manufacturing Company - Reyes, Richmond Ryan (College of Engineering, 2001)
Imperial Plastic Manufacturing Company is a small, product-oriented company dedicated in producing varieties of artificial plants, flowers and other components. Its size and nature make it ideal for a methods engineering study. The study documented existing systems and procedures, analyzed relevant problem areas, and used various techniques to generate alternatives. In order to fully understand the company and its operations, interviews, plant visits, production inspections and work study were conducted. After thorough observations and complete documentations, the study identified LOW PRODUCTION OF FINISHED GOODS as the main problem of the company. Using several work study techniques, the company's storage facilities and plant layout were improved. A new method of keeping inventory was also introduced. The company was also advised to sell unused machines and replace them with newer and better models for improved condition. The company was also advised to keep a maintenance schedule for these machines for better performance. The alternatives recommended were developed in order for company to improve and increase their production. The cooperation of the workers is essential in the implementation plan to ensure that they can work within the framework set by the management of the company. The implementation plan shows the estimated time frame the company will need to effect the proposed changes.